The public sector's role in Norwegian network cooperation: triple helix or laissez-faire? - Øyvind Heimset Larsen; Jon Gunnar Nesse; Synnøve Rubach (Triple Helix, 2018)
The concept of triple helix (TH) cooperation was introduced about two decades ago, as a method of enhancing innovation and value creation. A good networking practice for knowledge-based development should identify the correct balance between business, research and government. The TH model for cooperation embodies an argument for public initiatives in business networks. The purpose of this paper is to test the public role in TH efforts in Norway. This paper therefore poses the following question: What is the public sector's role in network development and cooperation in Norway when the initiative is based on the triple helix model? Data from five different business networks in Norway has been collected and analysed to answer this question. The results indicate that the public engagement in the different networks varied with the life cycle phase of the network and the public sector's position in the value chain. The balance between the public and private sphere may vary from as little engagement as possible (laissez-faire) to being an equal TH partner.
Keywords: 330; Norwegian Innovation Clusters programme; Public role; Triple helix